SEARCH FOR SELF IDENTITY IN SHASHI DESPANDE’S NOVELS - SARAVANAN.V; MS.M.GAYATHRI; R.UMA MAGESHWARI; MALATHI.V.P; A.MAHENDRAN (International Journal of Psychosocial Rehabilitation, 2020)
Literature is a river which flows on unbroken from one age to another. Writers who belong to one age continue to write far into the following age. Literary trends and movements overflow from one literary epoch into another, there is much overlapping and there are no water shutters to control it. Literature to be appreciated and enjoyed mustbe viewed as a whole. It is not the result of calculating the profit or loss involved in resisting the tastes of the multitude; it is the exposition of the artist and impact it is the real experience the artist. It takes up themes from everyday life and treats them in such a way that we get glimpses of a better life. All great literature is the bond that connects man with man; it renders man-made boundaries devoid of meaning, and another object of literature is to inspire and elevate man and alter the set up of his mind. Indian literature is very older than that of the Himalayas. Ancient India was highly advanced in literature, philosophy, religion, science, music and the performing arts.